A novel online rheometer for elongational viscosity measurement of polymer melts. (April 2016) - Köpplmayr, Thomas; Luger, Hans-Jürgen; Burzic, Ivana; Battisti, Markus G.; Perko, Leonhard; Friesenbichler, Walter; Miethlinger, Jürgen
Abstract: This paper focuses on the measurement of elongational viscosity of polymer melts and filled compounds using a novel online rheometer. We developed a device with two slit sections and a hyperbolic contraction part in between, which allows for constant monitoring of both shear and elongational viscosity during an extrusion process. Due to the favorable design of the hyperbolic contraction, pressure transducers can be incorporated directly into the flow channels, which prevents material accumulation in pressure holes. The results of a pipe-grade polypropylene random copolymer melt are in good accordance with Sentmanat Extensional Rheometer (SER) measurements, in contrast to other methods such as Cogswell analysis of High Pressure Capillary Rheometer (HPCR) data or measurement on a wedge-shaped slit die, which fail to predict the true non-Newtonian behavior of the melt. In addition, we present the results of a polypropylene homopolymer intended for thermoformed packaging applications, a glass fiber and a talc compound, which could all be successfully characterized using our rheometer.